2016
DOI: 10.3892/or.2016.4836
|View full text |Cite
|
Sign up to set email alerts
|

Development of a novel microbubble-liposome complex conjugated with peptide ligands targeting IL4R on brain tumor cells

Abstract: Gas (SF6)-filled microbubbles (MBs) were prepared by emulsion and solvent-evaporation method. The prepared MBs were further conjugated with doxorubicin (Dox)-loaded nano-sized liposome and peptide ligands to interleukin-4 receptor (IL4R) for targeting brain tumor cells. The final MB-liposome (Dox)-IL4R targeting peptide ligand [MB-Lipo (Dox)-IL4RTP] had a spherical structure with the mean size of 1,500 nm. The MB-Lipo (Dox)‑IL4RTP exhibited cellular uptake in U87MG brain tumor cells (a brain tumor cell line ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
35
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 24 publications
(35 citation statements)
references
References 30 publications
0
35
0
Order By: Relevance
“…Vadevoo et al reported that they synthesized an IL4R-targeting peptide (IL4RPep-1-K) conjugated with the proapoptotic peptide (KLAKLAK)2 and demonstrated this peptide exerted the selective anti-cancer effect against IL4R-expressing tumor in vitro and in vivo (4T1 breast tumor-bearing mice model) [11]. In fact, our laboratory has been developing the novel drug delivery system using ultrasound and microbubble-liposome complex with IL4RPep-1-K to detect and treat IL4R-expressing tumor [66].…”
Section: Discussionmentioning
confidence: 99%
“…Vadevoo et al reported that they synthesized an IL4R-targeting peptide (IL4RPep-1-K) conjugated with the proapoptotic peptide (KLAKLAK)2 and demonstrated this peptide exerted the selective anti-cancer effect against IL4R-expressing tumor in vitro and in vivo (4T1 breast tumor-bearing mice model) [11]. In fact, our laboratory has been developing the novel drug delivery system using ultrasound and microbubble-liposome complex with IL4RPep-1-K to detect and treat IL4R-expressing tumor [66].…”
Section: Discussionmentioning
confidence: 99%
“…Peptide-liposome bioconjugate systems can often be combined and used with other technologies for a dual-purpose drug delivery system. Park and colleagues established a novel microbubble-liposome complex conjugated to interleukin-4 receptor (IL4R)-targeting peptide ligands for theranostic treatment of brain tumors ( Figure 6A) [112]. In this study, DSPE-PEG-PDP liposomes were prepared using thin-film hydration and remote-loaded with DOX via an ammonium sulfate gradient.…”
Section: Peptide-liposome Bioconjugatesmentioning
confidence: 99%
“…Microbubbles (micrometer-sized bubbles, MBs) and melanin nanoparticles (MNPs) are emerging biocompatible materials for the diagnosis of various diseases and represent a safer and more effective alternative to conventional contrast agents. 16 MBs are generally composed of a hydrophobic gas-filled core and shell of lipids. They can generate echogenicity with US at a certain frequency owing to the absorption and reflection property of US waves and nonlinear oscillation.…”
Section: Discussionmentioning
confidence: 99%
“…Microbubbles (micrometer‐sized bubbles, MBs) and melanin nanoparticles (MNPs) are emerging biocompatible materials for the diagnosis of various diseases and represent a safer and more effective alternative to conventional contrast agents . MBs are generally composed of a hydrophobic gas‐filled core and shell of lipids.…”
Section: Discussionmentioning
confidence: 99%